De novo genome assembly of the white-spotted flower chafer (Protaetia brevitarsis). Issue 4 (5th April 2019) - Wang, Kui; Li, Pengpeng; Gao, Yongyang; Liu, Chunqin; Wang, Qinglei; Yin, Jiao; Zhang, Jie; Geng, Lili; Shu, Changlong
Abstract: Background: Protaetia brevitarsis, commonly known as the white-spotted flower chafer, is an important Scarabaeidae insect that is distributed in most Asian countries. Recently, research on the insect's harmfulness to crops, usefulness in agricultural waste utilization, edibility, medicinal value, and usability in insect immunology has provided sufficient impetus to demonstrate the need for a detailed study of its biology. Herein, we sequenced the whole genome of this species to improve our understanding and study of P. brevitarsis . Findings: We developed a highly reliable genome resource for P. brevitarsis (Lewis, 1879; Coleoptera: Cetoniinae) using Illumina and PacBio sequencing platforms. A total of 135.75 gigabases (Gb) was generated, providing 150-fold coverage based on the 810-megabases (Mb) estimated genome size. The assembled P. brevitarsis genome was 751 Mb (including the scaffolds longer than 2 kilobases (kb)) with 327 scaffolds, and the N50 length of the assembly was 2.94 Mb. A total of 34, 110 (22, 229 in scaffolds and 11, 881 located in alleles) genes were identified using Evidence Modeler, which was based on the gene prediction results obtained from 3 different methods ( ab initio, RNA sequencing based, and known gene based). Conclusions: We assembled a high-quality P. brevitarsis genome, which will not only provide insight into the biology of the species but also provide a wealth of information that will inform researchers on the evolution, control, and utilization of P. brevitarsis .